9 - La formation d’un espace public camerounais à l’épreuve de la construction des réseaux routiers de communication - Keutcheu, Joseph (Africa Development, 2021)
The central issue of this article is as follows: Can a public space be built and consolidated in Cameroon without the physical integration of its territory, without communications networks? In answering this question, we envisage communications networks as vectors for imposing government control on the territory and, simultaneously, as a way of forming a network of civil society actors that often denigrate the public authorities. In so doing, through the uneven spatial distribution of communication networks and the revelation of an archipelago society, we highlight the baroque configuration of Cameroonian public space.